Evaluasi Penerapan Kualitas Sistem Informasi Manajemen Rumah Sakit - Adelia, Adelia; Girsang, Ermi; Nasution, Ali Napiah (Journal of Telenursing (JOTING), 2024)
The purpose of this study is to evaluate the quality of the management information system at the UPTD RSUD. This research method is quantitative with a cross-sectional study design. The benefits of this study are to be a reference for hospital management to improve the quality of the hospital management information system. The results show that there is a relationship between infrastructure and the quality of the hospital management information system, human resources and the quality of the hospital management information system, procedures and the quality of the hospital management information system. Conclusion: There is a significant relationship between infrastructure, human resources, procedures and the quality of hospital management information systems. Keywords: Infrastructure, Quality, Procedures, Human Resources, Hospital Management Information System